FRAMING POWER AND IDEOLOGY IN PRABOWO SUBIANTO'S PRESIDENTIAL SPEECH - Nasrullah, Riki; Budiman, Arip; Prayogi, Arditya; Yuliyanto, Andik; Parmin, Parmin; Isam, Hishamudin (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
Political speeches function not only as formal addresses but also as powerful tools for constructing ideological narratives, legitimizing authority, and influencing public opinion. In a politically polarized and socially diverse country like Indonesia, presidential discourse plays a crucial role in uniting disparate groups and articulating visions for national development and reform. This study critically examines how President Prabowo Subianto frames power and ideology in his 2024 inaugural presidential speech by investigating the linguistic strategies and discursive mechanisms used to construct an image of inclusive leadership, address systemic corruption, and reinforce national identity. Employing a qualitative approach grounded in Critical Discourse Analysis (CDA), the research integrates van Dijk’s theory of power and ideology, Fairclough’s modality theory, Wodak’s critical pragmatics, Lakoff and Johnson's conceptual metaphor theory, and Moscovici's theory of social representation. The primary data consists of the official transcript of Prabowo's speech, retrieved from government sources and analyzed through purposive sampling to identify ideologically salient segments. These were manually coded for modality, speech acts, metaphorical constructions, and group representations. The analysis reveals that Prabowo constructs an assertive yet inclusive leadership persona by using a high-certainty modality to project confidence in achieving national goals, particularly food and energy self-sufficiency. Deontic expressions frame these goals as collective moral obligations. Assertive and commissive speech acts function to inform and mobilize, reinforcing his credibility and political commitment. Conceptual metaphors such as "journey" and "disease" simplify complex challenges, portraying national development as a shared path forward and corruption as a harmful condition requiring urgent cures. Through social representation, the speech elevates "the lower class" (e.g., farmers, fishermen) as national heroes while depicting corrupt elites as threats to societal well-being. These linguistic strategies form a coherent populist narrative that legitimizes reformist leadership and appeals to collective identity. This study contributes to the field of political discourse analysis in Indonesia by offering a comprehensive, multi-theoretical lens to unpack the ideological functions of language in presidential communication. It also holds practical implications for political speechwriting, civic education, and public engagement by demonstrating how language can be used to construct legitimacy, inspire unity, and frame national priorities in morally persuasive ways.